2021
DOI: 10.1002/mar.21530
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the interplay of device type, product familiarity, and shopping motivations on the accuracy of product size estimations in e‐commerce settings

Abstract: Research on diverging device conditions remains scarce, particularly in relation to how they affect online shoppers' product assessments. This research investigates the effects of online shoppers' device type on the accuracy of their product size evaluations and reveals, for the first time, the complex mechanisms behind these effects by examining the role of confidence about product size, product familiarity, and shopping motivations. The findings from four experimental studies show that using a PC (vs. a smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Perception of quantity stems from automatic processing (Dehaene, 2011; Mandler & Shebo, 1982), and is susceptible to multiple situational factors (Adaval, 2013; Koo & Suk, 2016; Madzharov & Block, 2010). As summarized in Table 2, in addition to the number of units (the numerosity effect; Adaval, 2013; Bagchi & Davis, 2016; Lembregts & Pandelaere, 2012; Monga & Bagchi, 2011; Pandelaere et al, 2011), these factors also include container height (Chandon & Ordabayeva, 2009; Koo & Suk, 2016; Raghubir & Krishna, 1999), package shape (Folkes & Matta, 2004; Sevilla & Kahn, 2014), color saturation (Hagtvedt & Brasel, 2017; L. Wang et al, 2020), visual design complexity (Garber Jr. et al, 2008; Sohn et al, 2017), product image on package (Madzharov & Block, 2010), assortment variety (Redden & Hoch, 2009), assortment structure (Ginsburg, 1978, 1980, 1991; Krishna & Raghubir, 1997), display device (Chung & Karampela, 2021), product/screen display orientation (Schmidt & Maier, 2019) and attitude ambivalence (Cornil et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Perception of quantity stems from automatic processing (Dehaene, 2011; Mandler & Shebo, 1982), and is susceptible to multiple situational factors (Adaval, 2013; Koo & Suk, 2016; Madzharov & Block, 2010). As summarized in Table 2, in addition to the number of units (the numerosity effect; Adaval, 2013; Bagchi & Davis, 2016; Lembregts & Pandelaere, 2012; Monga & Bagchi, 2011; Pandelaere et al, 2011), these factors also include container height (Chandon & Ordabayeva, 2009; Koo & Suk, 2016; Raghubir & Krishna, 1999), package shape (Folkes & Matta, 2004; Sevilla & Kahn, 2014), color saturation (Hagtvedt & Brasel, 2017; L. Wang et al, 2020), visual design complexity (Garber Jr. et al, 2008; Sohn et al, 2017), product image on package (Madzharov & Block, 2010), assortment variety (Redden & Hoch, 2009), assortment structure (Ginsburg, 1978, 1980, 1991; Krishna & Raghubir, 1997), display device (Chung & Karampela, 2021), product/screen display orientation (Schmidt & Maier, 2019) and attitude ambivalence (Cornil et al, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, consumers estimate quantity on the basis of the magnitude of individual items and thereby infer higher quantity from larger numbers (i.e., the numerosity effect; Adaval, 2013; Bagchi & Davis, 2016; Lembregts & Pandelaere, 2012; Monga & Bagchi, 2011; Pandelaere et al, 2011). Moreover, product package features (e.g., height, shape, color saturation, visual design, and product image on package) (Folkes & Matta, 2004; Hagtvedt & Brasel, 2017; Madzharov & Block, 2010; Raghubir & Krishna, 1999; Sohn et al, 2017), assortment features (e.g., assortment variety and assortment structure) (Ginsburg, 1980; Redden & Hoch, 2009), product display mode (e.g., display device and screen/product orientation) (Chung & Karampela, 2021; Schmidt & Maier, 2019), and consumers' attitude ambivalence (Cornil et al, 2014) all affect consumers' perceived quantity. Adding to these empirical findings, we focus on one of the most fundamental visual design elements that have not previously been examined—a dividing line—and investigate its effects on consumers' perceived quantity of items that are divided by the line.…”
Section: Introductionmentioning
confidence: 99%
“…research of Chung and Karampela (2021), we calculated the size perception error to reflect the influence of depth of field on product size perception.…”
Section: Study 4: the Moderating Role Of Product Familiaritymentioning
confidence: 99%
“…Product familiarity refers to the amount of experience and knowledge about a product accumulated by consumers (Alba & Hutchinson, 1987; Chung & Karampela, 2021). Previous research has demonstrated that compared to consumers with less product‐related experience (i.e., lack of familiarity with the products), those who are familiar with the products could better recall the product information (Alba & Hutchinson, 1987), identify the unique features of the products (Zhou & Nakamoto, 2007), and recognize the accurate attributes of the products (Krishen et al, 2016).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation